FERTILIZATING FREQUENCY OF SOYABEANS COMPOST TO THE GROWTH OF SENTANG SEEDLINGS (Azadirachta excelsa (JACK) M. JACOBS) - Arifa Mulyesthi Rahmawathi; Nurheni Wijayanto; Andhira Trianingtyas (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
One of less known timber species is Azadirachta excelsa (Jack) M. Jacobs known with the trading name as Sentang. Fertilizer as a nutrient supply was given to gain high quality seedlings. One of organic material which can be utilized as organic fertilizer is the waste of soybeans harvesting. Soybeans waste could be used as compost. This research aimed to examine the fertilizing frequency of soybeans compost to the growth of Sentang seedlings and compare them with cow manure fertilizer fertilizer. The frequency of fertilizing used were once a week, once in two weeks, once in three weeks, and once in four weeks during 12 weeks observation. The result shows that fertilizing soybeans compost to the Sentang seedlings once in two weeks give significant impact to the growth of diameter, height, total wet mass, total dry mass, and root-crown ratio of Sentang. Key words: Azadirachta excelsa, frequency fertilizing, soybeans compost